Effect of temperature on the performance of aqueous redox flow battery using carboxylic acid functionalized alloxazine and ferrocyanide redox couple - Chu, Cheunho; Kwon, Byeong Wan; Lee, Wonmi; Kwon, Yongchai (The Korean journal of chemical engineering, 2019)
Carboxylic acid functionalized alloxazine (alloxazine-COOH) and ferrocyanide are utilized as active species for aqueous redox flow battery (ARFB), and the effect of operating temperature on the performance of ARFB was investigated. Based on electrochemical characterization, although ferrocyanide is in a quasi-reversible state at room temperature, the state becomes irreversible as temperature increases. By the use of carbon felt (CF) containing carbon-oxygen functional groups, the activity of ferrocyanide is enhanced without side effect, such as irreversible redox reactivity. This is because the hydrophilic (charge-dipole) interaction between dipole groups (hydroxyl and carbonyl groups) onto CF and ferricyanide ions promotes the oxidation reaction of ferricyanide. Though alloxazine-COOH coated on glassy carbon electrode shows irreversible state compared to ferrocyanide as temperature increases, the activity of alloxazine-COOH is also enhanced by using the hydrophilic group doped CF. To prove whether the redox reactivity of the two active species is improved with increase in temperature, the performance of ARFBs using them was evaluated in the different temperature conditions. When the temperature of both anolyte and catholyte is 45 °C, average discharge capacity and state of charge are 24 Ahr·L −1 and 90%, and the values are reduced to 23 Ahr·L −1 and 86% in ARFB of only catholyte heating, 22 Ahr·L −1 and 82% in ARFB of only anolyte heating and 21.3 Ahr·L −1 and 80% with no heating. Based on that, it is speculated that the operation temperature can be a factor in determining the performance of ARFB.